2003
DOI: 10.1093/molehr/gag066
|View full text |Cite
|
Sign up to set email alerts
|

Fibroids display an anti-angiogenic gene expression profile when compared with adjacent myometrium

Abstract: The aetiology of uterine fibroids remains unknown, despite causing significant gynaecological morbidity. Fibroids have a reduced microvascular density when compared with adjacent myometrial tissue. The aim of this study was to identify genes with differential expression between fibroid and adjacent normal myometrium, particularly genes with a role in angiogenesis. Total RNA was extracted from fibroid/myometrium pairs from 12 hysterectomy specimens, and used to perform 24 cDNA microarrays. There were 10,500 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 33 publications
1
55
1
3
Order By: Relevance
“…Over-expression of IGF-2 in fibroids has been identified in many independent global gene profiling analyses (15)(16)(17)(18)(19)(20)(21). Insulin-like growth factor-2 is one of a few growth factors identified by global transcription profiling as up-regulated, and the level of its over-expression is generally in the range of a two-to threefold increase in fibroids compared with matched myometrium (5).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Over-expression of IGF-2 in fibroids has been identified in many independent global gene profiling analyses (15)(16)(17)(18)(19)(20)(21). Insulin-like growth factor-2 is one of a few growth factors identified by global transcription profiling as up-regulated, and the level of its over-expression is generally in the range of a two-to threefold increase in fibroids compared with matched myometrium (5).…”
Section: Figurementioning
confidence: 99%
“…The mitogenic role of IGF-1 in fibroid growth has been reported both in vitro and in vivo (10)(11)(12). As a potent mitogenic factor (13), IGF-2 was reported to be overexpressed in fibroids in 1990 (14), and recent global gene transcription profiling analyses have supported the speculation that it is one of few genes constantly over-expressed in fibroids (15)(16)(17)(18)(19)(20)(21). However, the function and regulation (22)(23)(24) of IGF-2 in fibroids are largely unknown.…”
mentioning
confidence: 99%
“…Weston et al found that these fibroids have an anti-angiogenic expression profile (6), which may explain the reduced microvascular density observed in fibroids relative to the myometrium. Furthermore, a review of gene expression data revealed concordant changes in the genes regulating retinoid synthesis, insulin-like growth factor metabolism, transforming growth factor signaling and extracellular matrix formation (7).…”
Section: Introductionmentioning
confidence: 99%
“…Gene array studies have been conducted to clarify the alteration of gene expression profiles in uterine leiomyoma and have identified numerous genes for which expression is up-or down-regulated compared with levels in normal myometrium (Tsibris et al 2002, Catherino et al 2003, Chegini et al 2003, Skubitz & Skubitz 2003, Wang et al 2003, Weston et al 2003, Hoffman et al 2004, Quade et al 2004. Although the total number of genes analyzed in each array has varied, 5-358 genes per study have been identified as down-regulated in leiomyoma, greatly exceeding the number of up-regulated genes in eight out of nine independent array-based studies (Tsibris et al 2002, Ahn et al 2003, Catherino et al 2003, Chegini et al 2003, Skubitz & Skubitz 2003, Wang et al 2003, Weston et al 2003, Quade et al 2004, Arslan et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Although the total number of genes analyzed in each array has varied, 5-358 genes per study have been identified as down-regulated in leiomyoma, greatly exceeding the number of up-regulated genes in eight out of nine independent array-based studies (Tsibris et al 2002, Ahn et al 2003, Catherino et al 2003, Chegini et al 2003, Skubitz & Skubitz 2003, Wang et al 2003, Weston et al 2003, Quade et al 2004, Arslan et al 2005. Downregulated genes would play an important role in leiomyoma phenotype, similar to or more important than up-regulated genes.…”
Section: Introductionmentioning
confidence: 99%